The effect of a soft drink tax in Mexico: evidence from time‐series industry data. (19th January 2021) - Arteaga, Julio C.; Flores, Daniel; Luna, Edgar
Abstract : We use a time‐series approach and industry data to estimate the effect on consumption of a relatively large excise tax on soft drinks imposed recently in Mexico. The tax caused a price increase of 12.8 per cent and reduced per‐capita consumption about 3.8 per cent. This effect is small in comparison with the effects that are suggested by most studies that estimate price elasticities using an almost ideal demand system and household survey data. Moreover, we find that the effects of the tax on consumption vary throughout the year. The effect of the tax tends to be higher in the winter but vanishes during the summer. We also find that the effect of the tax does not vary from one year to another.